Understanding the Determinants of Who Gets Laid Off: Does Affective Organizational Commitment Matter?. Issue 6 (24th January 2015) - Zatzick, Christopher D.; Deery, Stephen J.; Iverson, Roderick D.
Abstract : Whereas prior research has focused on structural, demographic, and human capital factors to predict who gets laid off, the current study examines affective organizational commitment as an additional attribute related to an employee's layoff chances. Specifically, we investigate the relationship between affective organizational commitment and an individual's layoff chances, as well as whether this relationship differs between high and low performers. Event history analysis is conducted using survey data with matched personnel records from 3, 057 employees across 563 Australian bank branches. After controlling for numerous predictors of layoffs, the results demonstrate that affective organizational commitment decreases the likelihood of an employee being laid off. Further, the effects of affective organizational commitment on an individual's layoff chances are greater for lower performers than higher performers. We discuss the implications of these findings for researchers and practitioners. © 2015 Wiley Periodicals, Inc.